War and Financial Statements: Assessing the Impact of the Russia-Ukraine Conflict on International Accounting and Reporting Standards - Noy, Ismail; Dabamona, Jufri (Advances in Applied Accounting Research, 2024)
Purpose: This study aims to assess the impact of the Russia-Ukraine conflict on international accounting and reporting standards. The focus is on understanding how geopolitical tensions influence regulatory divergence, enforcement challenges, financial reporting practices, and market dynamics. Research Design and Methodology: A qualitative methodology was employed, involving a systematic review of scholarly articles, books, reports, and other academic sources. Data were collected through comprehensive searches of databases, including Google Scholar and JSTOR, with thematic analysis employed to identify recurring themes and patterns. Triangulation, member checking, and reflexivity ensured the validity and reliability of the findings. Findings and Discussion: The findings reveal that the Russia-Ukraine conflict exacerbates regulatory divergence, complicates the enforcement of international accounting standards, and increases the complexity of financial reporting. Geopolitical tensions lead to fragmented regulatory responses, undermining efforts toward harmonization. Corporations adopt enhanced risk disclosures and conservative reporting approaches to navigate uncertainties and reassure stakeholders. Investor sentiment and market perceptions are significantly influenced, resulting in increased market volatility and shifts in investment strategies. Implications: This study highlights the need for adaptive regulatory responses and collaborative efforts to promote the harmonization of accounting standards. Technological innovations, such as blockchain and artificial intelligence, offer promising avenues for enhancing regulatory compliance and transparency. The findings underscore the importance of interdisciplinary research and longitudinal studies in informing policy interventions, corporate strategies, and regulatory reforms, promoting financial stability, transparency, and resilience in conflict-affected environments.